Analysis of the c3Pi (v = 0, 1) State on the Basis of the 3A Band System in the 12C16O, 13C16O, and 14C16O Molecules - Hakalla, Rafał (2000 Academic Press (Journal of Molecular Spectroscopy), 2001)
The 1-0, 1-1, and 1-2 bands of the 3A system of 13CO (c3Π-a3Π) have been recorded for the first time, in the form of discharge emission spectra photographed at high resolution. Preliminary rotational analysis suggests that the v = 1 level of the c3Π state is perturbed in a fashion similar to the v = 0 level, previously observed by Dabrowski et al. (1987. I. Dabrowski, M. Vervolet, and D. C. Wang, Can. J. Phys. 65, 1171-1177). Rotational combination differences from the 1720 measured lines have been used to obtain rotational constants for the v = 0-2 levels of the a3Π state, using the Hamiltonian of Brown et al. (1979. J. M. Brown, E. A. Calbourn, J. K. G. Watson, and F. D. Wayne, J. Mol. Spectrosc. 74, 294-318). and the least squares formalism of Curl and Dane (1988. J. Mol. Spectrosc. 128, 406-412), as modified by Watson (1989. J. Mol. Spectrosc. 138, 302-308). Term values for the c3Π, v = 1 level have then been obtained from the line frequencies, and a set of effective rotational constants for the c3Π (v = 1) level of 13CO has been derived. © 2000 Academic Press.
Keywords: High resolution molecular spectroscopy; carbon monoxide; the 3A band system; c3Pi(v=1) state